Pengaruh Penerapan SIMDA Keuangan Terhadap Kualitas Laporan Keuangan: Studi Kasus Pada Rumah Sakit Khusus Gigi Dan Mulut Kota Bandung - Dedi Karmana; Sakti Muda Nasution; Mira Ismirani Fudsy; Budi Lesmana (Center of Research, STIE Pasundan, Bandung, Indonesia., 2022)
The purpose of this research are to know the application of SIMDA Finance at the Rumah Sakit Khusus Gigi dan Mulut in Bandung city, the results of the SIMDA Financial report and how the influence of the application of SIMDA Finance to the Quality of Financial Reports at the Rumah Sakit Khusus Gigi dan Mulut in Bandung city. The research method used is descriptive quantitative method. Data obtained from questionnaires distributed and then processed through SPSS 25 to be tested and then presented the results of the output. After analyzing and discussing, the authors conclude that the implementation of SIMDA Finance at RSKGM is good even though there are still obstacles. The output of SIMDA Finance is complete and of high quality which contains relevant, reliable, comparable and understandable information in accordance with PP. 71 of 2010 concerning Government Accounting Standards. SIMDA Finance has a positive and significant effect on the Quality of Financial Reports at the Rumah Sakit Khusus Gigi dan Mulut in Bandung City and the magnitude of the influence of SIMDA Finance on the Quality of Financial Reports is 58.3% and the remaining 41.7% is influenced by other variables outside of this study.